Antidepressants and hypertensive disorders in pregnancy: a retrospective cohort analysis - Breadon, Carolyn; Arunogiri, Shalini; Turbić, Alisa; Lavale, Alex; Maldonado, Ricardo; Kulkarni, Jayashri (Frontiers in Psychiatry, 2025)
ObjectiveThis retrospective cohort study investigated relationships between antidepressant use in pregnancy and hypertensive disorders of pregnancy.Design/setting/sampleObservational cohort study examining births in an outer-metropolitan maternity hospital in Australia between 2008-2022. 75,308 births were examined.MethodsLogistic regression analysis considering covariates including maternal age, smoking, BMI, depression, anxiety, schizophrenia or bipolar disorder, gestational diabetes, pre-pregnancy diabetes. The antidepressant treatment cohort was compared with two groups: all births at this hospital within this time period, and a more closely matched depressed/anxious cohort not treated with antidepressants in pregnancy. The overall group of women taking antidepressants in pregnancy was also compared with women taking antihypertensive medications in pregnancy.Main outcome measuresClinical diagnoses of hypertension, pre-eclampsia or eclampsia recorded in pregnancy, at birth or the immediate postpartum, as well as treatment with antihypertensive medication.ResultsA statistically significant relationship (p = 0.001) between antidepressant use in pregnancy and clinically diagnosed hypertension, OR 2.65, CI 1.45-4.81, when compared with the overall birthing cohort. When covariates were added, including BMI, age and gestational diabetes, this relationship lost statistical significance. The relationship was also non-significant when a depressed/anxious cohort was used as the comparator group: OR 1.49 (p = 0.24, CI 0.77 – 2.88). A highly statistically significant relationship was found between antenatal antidepressant use and pre-eclampsia, OR 2.90, (p < 0.0005, CI 2.1 – 4.0), which retained significance when covariates were added to the regression analysis (OR 2.07, CI 1.45-2.97, p < 0.0005). BMI and gestational diabetes were also significant risk factors for pre-eclampsia in this sample. As in other research, depression was also found to be related to pre-eclampsia at a borderline significant level (p = 0.086). Considering the co-administration of antidepressants and antihypertensive medications, a strong relationship was found: OR 2.90, p < 0.000, CI 2.13-3.94, aOR 2.02 p < 0.000, CI 1.39-2.93. When women taking antidepressants were compared with depressed/anxious peers a similarly significant relationship between antidepressant use and hypertension of pregnancy was found: OR 2.56, (p < 0.0005, CI 1.7 – 3.7). We found a highly significant relationship between antidepressant use and eclampsia, OR 2.84 (p < 0.0005, CI 2.06 – 3.92), unchanged when compared with the depressed/anxious cohort: OR 2.84 (p < 0.0005, CI 2.06 – 3.92).ConclusionsThis study supports existing research suggesting a strong relationship between antidepressant use in pregnancy and hypertensive disorders. Comparison with a depressed/anxious cohort reduces the risk that these underlying conditions could contribute to this finding.